Hb AHVAZ [α83(F4)Leu→Arg, CTG>CGG (α2); HBA2: c.251T>G], A New Hemoglobin Variant of the α2-Globin Gene. (October 2013) - Hamid, Mohammad; Shariati, Gholamreza; Saberi, Alihossein; Galehdari, Hamid; Kaikhaei, Bijan; Mohammadi-Anaei, Marziye
<x xml:space="preserve">Abstract</x> We report a novel mutation on the α2-globin gene, codon 83 (T>G), which was detected in two members of two unrelated families from Khuzestan Province, South Iran, that we named Hb Ahvaz. This mutation was detected by cellulose acetate electrophoresis and characterized by molecular studies. Hb Ahvaz does not seem to be responsible for hematological abnormalities in the carriers, but with α0-thalassemia (α0-thal) defects, might induce severe clinical symptoms.